Chemical Composition and Microbial Contaminants of Poha Beer: A Local Nonalcoholic Beverage in the Bolgatanga Municipality, Ghana - Julius T. Dongdem; James Abugri; Clement A. Asakedola (International Journal of Microbiology)
Microbial and physicochemical analysis was performed on randomly sampled Poha Beer manufactured and vended in the Bolgatanga Municipality, Ghana. Poha Beer as it is referred to in Dagbani, is a Tamarindus indica fruit extract, a local nonalcoholic beverage originally processed and sold by rural women of the Dagomba ethnic descend. Morphological examination of bacterial cultures, Gram staining, and biochemical confirmatory tests were used to detect the presence of microbial pathogens in 45 samples of Poha Beer. A refractometer, a flame photometer and an atomic absorption spectrometer were used for the elemental analysis. All Poha Beer samples obtained from the Bolgatanga Municipality were positive for yeast, E. coli, Enterobacter sp. and Bacillus cereus. Pb was not detected in any of the samples. Chemical components detected include Zn2+ (average, 0.154 mg/L), Cd2+ (0.056 mg/L), Na+ (1.723 mg/L), Ca2+ (2.262 mg/L) and K+ (3.96 mg/L). All samples were acidic with an average pH value of 3.55. The Brix value of samples, however, was between 9.0 and 11.4 % per 40 mL of Poha Beer. Therefore, Poha Beer processed and sold in the Bolgatanga Municipality is acidic and contains detrimental amounts of Cd2+ and bacterial pathogens which may render it unwholesome for human consumption.